"Fortunately I felt pain, or I would have thought I was on my way out": experiencing pain and negotiating analgesic treatment in the context of cancer. Issue 2 (4th March 2023) - Restivo, Léa; Dudoit, Éric; Duffaud, Florence; Salas, Sébastien; Dany, Lionel
Abstract: Objectives: To explore cancer patients' experience of pain and coping strategies as well as beliefs and representations associated with pain, pain management and treatments. Method and participants: A qualitative study based on semi-structured interviews was conducted among 16 patients with cancer. The inductive research strategy adopted derived from the Grounded Theory approach and the data transcribed verbatim were gradually analyzed involving researcher triangulation. Findings: The experience of pain and the coping strategies developed by patients to deal with it are shaped by the experience and representations of cancer associated with death and suffering. Pain acts both as an indication to the patients that they are still alive and as an indicator of the progression of the disease. Cancer also models patients' relationships to analgesic treatments and health care providers, since pain is an area in which patients can take back control of what is happening to them. Patients' expression of reluctance to accept analgesic treatments is also influenced by the significance of opioid treatments in this context, which are perceived as an indication that the end of life is close. Conclusions: The contextualization of pain through the particularities of cancer is critical in order to understand cancer patients' experience of pain. Implications for psychosocial providers: Not only patients' knowledge but also the meaning-making of pain should be incorporated in interventions targeting pain management.